Fabrication of modified mesoporous carbons-coated monolith synthesized via evaporation-induced self- assembly approach for B-carotene adsorption - How, Cai Kian (2014)
A rapid synthesis procedure of mesoporous carbons coated monolith (MCCM) adsorbent have been accomplished by the mean of evaporative induced self-assembly (EISA) approach. Furfuryl alcohol acts as carbon precursor, triblock copolymer Pluronic F-127 as soft-template or pore-forming agent, pyrrole as binder for polymerization with nitric acid as catalyst and inorganic cordierite as substrate through dip-coating method. Boehm's acid-base titration experiment revealed dominance of acidic sites over surface of the adsorbents with majority of acidic active sites occupied by phenolic and carboxylic sites. The basicity remains unchanged after modification which is 0.0137mmol/g. Nitrogen adsorption isotherm indicated the representative Type IV isotherm which according to IUPAC classification, resemble mesoporous phase of carbonaceous materials. PSD curves showed bimodal pore sizes distribution of mesoporous carbon adsorbents with excessive acid catalyst and ethanol loading. Higher acid concentration yields fast condensation of polymeric resin during self-assembly process meanwhile excess of ethanol solvent detour the cross-linkage of polymeric materials thus leads to a decrease in adsorption capacities. The β-carotene adsorption capacity were varies between 179.60 (optimum) and 112.56 mg/g (lowest) under various experimental modification conditions. Therefore, adsorption properties: Isotherm, kinetics, and thermodynamics studies have been analyzed using MCCM adsorbent with composites of FA/ F-127/ HNO3/ EtOH/ Py at molar mass of 3/2.5/ 0.2/ 5/1. The adsorption kinetics of β-carotene onto MCCM adsorbent in isopropyl alcohol solution was investigated through two kinetic models, namely Largregren first-order and pseudo-second-order model. The adsorption kinetics exemplified the chemisorption of β-carotene onto MCCM adsorbent. Intra-particle diffusion featured the involvement in β-carotene adsorption mechanism however it is not the sole rate- limiting step. Two adsorption isotherm namely Langmuir and Freundlich models were used to establish the adsorption equilibrium data at temperature of 30 to 50 ºC. The adsorption experiments data were described better by Freundlich model which elucidated the heterogeneity of surface active sites over MCCM adsorbents with more effective adsorption process at higher temperature. The maximum adsorption capacity of β-carotene obtained was 192.64 mg/g at 50 ºC. The reusability of MCCM adsorbent after adsorption process have been conducted by several batch desorption process. A slight reduction in adsorption capacities have been observed after three consecutive regeneration cycles.